How is the Learning Evaluation of the Pythagorean Theorem?: A Systematic Literature Review - Aripin, Usman; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hendriana, Heris (FKIP Universitas Lampung, 2024)
Mathematics learning problems, especially on the Pythagorean theorem material, cannot be studied only from one side, but need to be seen comprehensively from various integrative learning studies. This study aims to provide an overview of the evaluation of learning Pythagorean theorem material from reputable studies. This research uses the Systematic Literature Review (SRL) method. A review was conducted of 13 relevant articles published in various reputable international journals in the period 2019 to 2024. The data analysis used was carried out with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Based on the results of the review, it was found that in the Pythagorean theorem material there are still many misconceptions of understanding, with implications for the ability of abstraction that is not optimal. The quality of teaching is influenced by teachers' motivational beliefs in teaching, technology integration can help increase learning motivation, streamline learning and students are happier with teachers who use learning media, and teacher motivation in applying technology has an important role. In the realm of learning innovation, problem-based learning with a realistic mathematics approach is proven to be valid and effective and encourages active students and positive responses to the Pythagorean theorem material. Evaluation instruments must be valid, reliable, well designed to be effective in optimizing the learning process and diagnosing learning difficulties. Keywords: pythagorean theorem, learning evaluation, mathematics learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp847-863